The Ottoman policy for maintaining stability in the Eyalet of Algiers according to the Mühimme Defteri documents of the 16th Century - BICHI , Rahima; GRIZA , Rabia (La Revue d’Histoire Méditerranéenne, 2024)
After Algeria was annexed to the Ottoman State in 1519, the latter sought to impose laws and regulatory measures to govern it, aiming to establish security and ensure internal stability. Given the Mediterranean circumstances at the time, which exposed the region to external threats, it became imperative for the Sublime Porte to pay close attention to Algeria, manage it with caution, and address the grievances of its inhabitants, which were frequently communicated to Istanbul. This study aims to critically examine and analyse the Mühimme Defteri Documents in order to highlight the efforts of Ottoman rulers in establishing security and maintaining internal stability within the Eyalet of Algeria. Additionally. the research seeks to refute the accusations made by detractors who alleged that the Ottoman presence in Algeria was marked by oppressive and brutal policies toward the local population. The study adopts a historical, inductive, and analytical approach, providing a rigorous examination of the insights derived from the Mühimme Defteri Documents. The findings of the study demonstrate the active role of the Sublime Porte in ensuring security and stability, suppressing Janissary mutinies, addressing the embezzlement of local funds, and enforcing accountability among officials who violated the established laws.